Synopsis of subtribe Hyptidinae (Lamiaceae) in Argentina - O'Leary, Nataly Cristina (2015)
In the present work a revision of Hyptidinae for Argentina is presented. In this country this subtribe is represented by 20 taxa: three Cantinoa species, three Condea species, 11 Hyptis species and one variety, and two Marsypianthes species; all taxa are native and just one of these is endemic to Argentina. Full descriptions, along with distribution information and illustrations are provided. Lectotypes are designated for the following 13 names: Clinopodium chamaedrys, Hyptis balansae, H. brevipes, H. brevipes var. vulgaris, H. cinerea, H. cinerea var. stenophylla, H. dumetorum var. inconcinna, H. lagenaria, H. lorentziana, H. muelleri, H. rugosula, Marsypianthes hassleri and Peltodon comaroides.